Under currents - Roberts, Nora (New York : St. Martin's Press, 2019)
"From the #1 New York Times bestselling author, a novel about the power of family to harm--and to heal. Within the walls of a tasteful, perfectly kept house in North Carolina's Blue Ridge Mountains, young Zane Bigelow feels like a prisoner of war. Strangers--and even Zane's own aunt across the lake--see his parents as a successful surgeon and his stylish wife, making appearances at their children's ballet recitals and baseball games. Zane and his sister know the truth: There is something terribly wrong. As his father's violent, controlling rages--and his mother's complicity--become more and more oppressive, Zane counts the years, months, days until he can escape. He looks out for little Britt, warning her: Be smart; Be careful. In fear for his very life, he plays along with the insidious lie that everything is fine, while scribbling his real thoughts in a secret journal he must carefully hide away. When one brutal, shattering night finally reveals cracks in the façade, Zane begins to understand that some people are willing to face the truth, even when it hurts. As he grows into manhood and builds a new kind of family, he will find that while the darkness of his past may always shadow him, it will also show him what is necessary for good to triumph--and give him strength to draw on when he once again must stand up and defend himself and the ones he loves..."--